13 days to glory : the siege of the Alamo - Tinkle, Lon. (College Station : Texas A & M University Press, 1985)
A day-to-day chronological investigation of the siege of the Alamo in 1836, discussing the circumstances that led each person to be inside the abandoned mission during the battle that claimed the life of frontiersman Davy Crockett.
Originally published; New York: McGraw-Hill, 1958.
Thirteen days to glory.
Includes bibliographical references (p. 248-252).
Keywords: Alamo (San Antonio, Tex.) -- Siege, 1836.; Texas -- History -- Revolution, 1835-1836.